S-colocalization and Adams cocompletion - Choudhury, Snigdha Bharati; Behera, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512 A relationship between the S-colocalization of an object and the Adams cocompletion of the same object in a complete small U-category (U is a fixed Grothendieck universe) is established, together with a specific set of morphisms S.